Nakaukit sa kasaysayan Bishop Antonio Fortich ([Quezon City] The Institute, 1989)
The life and times of Negros' known leader and Nobel Prize nominee, filmed on location, from the northern to the southern tip of Negros.
VHS.
Host, Ma. Ernie Selvido ; mga editor, Billy Belleza, Mar Belleza.
Keywords: Fortich, Antonio Y; Negros Occidental; Biography; Philippine history